Analisis Kepuasan Mahasiswa terhadap Outbound Clinic Sebagai Bagian dari Kurikulum Baitul Arqam - Hidayatullah, Kemal; Saleh, Khairul (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Baitul Arqam is an ideological cadre-building and character development program for students that serves as a distinctive feature of the cadre education system. One of the learning methods applied in the Baitul Arqam curriculum is the outbound clinic, which emphasizes experiential learning. This study aims to analyze participants’ satisfaction levels with the implementation of the outbound clinic as part of the Baitul Arqam curriculum for university students. The research employed a descriptive quantitative approach using a survey method. The research subjects were students participating in the Baitul Arqam program who attended the outbound clinic activities. The research instrument was a satisfaction questionnaire covering aspects of learning materials, facilitators, methods, facilities and infrastructure, and perceived benefits of the activity. The results indicate that, in general, participants’ satisfaction levels were in the high category, suggesting that the outbound clinic is effective as part of the Baitul Arqam curriculum in fostering character development, teamwork, leadership, and Islamic values among students. These findings recommend strengthening and further developing the outbound clinic as a contextual learning strategy within the Baitul Arqam curriculum.